2019
DOI: 10.1002/rev3.3170
|View full text |Cite
|
Sign up to set email alerts
|

Verbal reports in the reading processes of language learners: A methodological review

Abstract: This methodological review highlights the trends in empirical studies where a methodological construct (i.e. verbal reports) intersects with content (i.e. literacy research). Specifically, we synthesise research on language learners’ reading in which verbal reports were deployed as a methodological tool. Questioning the long‐standing assumption that verbal report methods validated in first‐language verbal report reading studies necessarily constitute a basis for validation of second‐language verbal report read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 100 publications
(315 reference statements)
0
2
0
Order By: Relevance
“…As translation involves reading and writing, related studies in these two fields merit our attention. Smith et al (2019) provided a methodological review of 76 original empirical studies published between 2000 and 2015 that used verbal reports (including TAPs) to investigate the reading processes of language learners; six of these studies discussed the reactivity of verbal reports. Leow and Morgan-Short (2004) and Bowles and Leow (2005) found that verbalization had a minimal effect on text comprehension and written production and did not compromise the validity of the study.…”
Section: Validity Of Tapsmentioning
confidence: 99%
“…As translation involves reading and writing, related studies in these two fields merit our attention. Smith et al (2019) provided a methodological review of 76 original empirical studies published between 2000 and 2015 that used verbal reports (including TAPs) to investigate the reading processes of language learners; six of these studies discussed the reactivity of verbal reports. Leow and Morgan-Short (2004) and Bowles and Leow (2005) found that verbalization had a minimal effect on text comprehension and written production and did not compromise the validity of the study.…”
Section: Validity Of Tapsmentioning
confidence: 99%
“…It was used to discover the lexical inferencing strategies that EFL learners used. Think aloud protocol was one of the most widely used tools in lexical inferencing strategy research by many researchers in a second or foreign language (Smith, Kim, Vorobel, and King, 2019;Nassaji, 2006;Cohen & Upton, 2007). The main purpose for using the technique of Think-aloud protocols is to get a clearer picture of what EFL learners are doing and thinking while reading an English text, specifying the knowledge sources they used to guess the meaning of unknown words.…”
Section: Think-aloud Protocolsmentioning
confidence: 99%